Secondary forests as biodiversity repositories in human-modified landscapes: insights from the Neotropics - Tabarelli, Marcelo; Santos, Bráulio Almeida; Arroyo-Rodríguez, Victor; de Melo, Felipe Pimentel Lopes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
In this essay we examine some of the processes affecting the composition and structure of tree species assemblages and, consequently, what we can expect from secondary-forest stands as an element of human-modified landscapes and as an opportunity for biodiversity persistence in this ecological context. Based on the available information, it is reasonable to predict that in some landscapes or biotas: (1) small forest remnants degenerate and support plant assemblages with attributes similar to those observed in early and intermediate-aged regenerating stands, while secondary-forest stands move from initial to more advanced successional stages; (2) collectively, remnant/stand attributes and landscape integrity define the pace through which degeneration proceeds, but also the potential for regeneration; (3) at the landscape spatial scale, remnants and stands tend to converge in terms of structure, but also in terms of taxonomic and functional composition. In other words, remnants degenerate and secondary-forest stands regenerate toward a sort of ‘climax community’, which is conditioned by the physical and biological integrity of both patch and landscape. Considering secondary forests in the conceptual, ecological and spatial framework of human-modified landscapes may help us to understand and maximize the conservation services provided by this habitat as it proliferates through human-modified landscapes.